Analyzing the Difficulties in Teaching Kindergarten - Aziza Oktavia; supiyarti supiyarti (Universitas Pahlawan Tuanku Tambusai, 2020)
This research was conducted to determine the difficulties in teaching young learners at the IT INSAN CENDEKIA BANGKINANG Elementary School. This research uses a qualitative interview method which aims to determine the difficulties teachers experience in teaching young learners in schools. There were two teacher gave response on their difficulites in teaching students in kindergarten. Interviews were conducted with two teachers at the school. From the two interviews conducted, competent teachers are needed.